Selby Tunnel upper portal (Minnesota Streetcar Museum, 1910)
83199373aab994cbb48ffb64201cfb17
Looking east at the streetcar tracks in the middle of Selby Avenue descending to the portal of the Selby Tunnel.
United States
Minnesota
Ramsey
Summit Hill
St. Paul
Mode of access: Internet.
Keywords: streetcars; Twin City Rapid Transit Co.; street scene; Transportation